Contribution à la connaissance de la topographie d’un centre paroissial en milieu rural : le cas de Joué-lès-Tours (Indre-et-Loire) - Pierre Papin; Jérôme Livet; Camille Vanhove; Françoise Yvernault (Revue Archéologique du Centre de la France)
The rescue excavation of Victor Hugo and François Mitterrand squares in the municipality of Joué-lès-Tours, France, conducted in 2011 and 2012 before the construction of the first tramway line of the urban area of Tours, provided the opportunity to document archeologically a rural ecclesial pole of a significant size. The object of the excavation was a Christian sanctuary destroyed in 1868, which was the religious and funeral centre of a rural parish during the Middle Ages and the modern period. In spite of relatively poor preservation in a present day urbanized context, the study of the Joué-lès-Tours site contributes to the knowledge of the topography of parish centres in rural areas. Through analysing the evolution of the site over a long period (7th-19th century), specifically in terms of the relations between church, funeral areas and settlement(s), this article addresses the question of how the structural framework of the parish was established during the Middle Ages.